Microbiology quality and shelf life analysis of enteral formulas based on tempeh flour and yam flour - Annisa, Wahyu Ilmi; Ardiaria, Martha; Rahadiayanti, Ayu; Fitranti, Deny Yudi; Dieny, Fillah Fithra; Afifah, Diana Nur; Nissa, Choirun (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: Critically ill patients have an increased risk of developing infection. Enteral formula that given to patients must meet food safety which includes microbiology quality. In powder form, powder formula is a solution to suppress microbial growth, although it is still susceptible to oxidation. Shelf life is useful to determine the oxidation status. Objectives: This study aimed to analyze the value of TPC, Salmonella, E. coli and shelf life of enteral formula.Methods: This study was a completely randomized experimental design of one factor, namely the length of storage for values of TPC, Salmonella and E. coli with variations in storage for 0, 1, 2, and 3 hours at room temperature. Data on the TPC test was analyzed using Kruskal-Wallis. The temperature used for shelf life with TBA based-Arrhenius equation is 250C, 350C, and 450C for 28 days.Results: There was a difference in the length of storage of 0, 1, 2, and 3 hours on the value of TPC. The TPC value at 0 and 1 hour did not exceed the normal limit. The value of Salmonella was negative/25 g and < 3/g for E. coli. The shelf life of enteral formulas was respectively 250C, 350C and 450C for 44.89, 28.26 and 18.32 days.Conclusion: The longer the length of storage, the higher the TPC value. In accordance with the Indonesian standard (SNI), there is no contamination of Salmonella and E. coli in the enteral formula. The longest shelf life is at 250C.